SOCIOEDUCAÇÃO: ENTRE A SANÇÃO E A PROTEÇÃO - Bonatto, Vanessa Petermann [UNESP]; Fonseca, Débora Cristina [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2020)
The objective of this article is to reflect on the sense of socioeducation and its contradictions in the practice of the social education counselor. For that, it analyses data of a qualitative research, which uses interviews and the understanding of the role of socio-educators in the Specialized Reference Centers in Social Assistance (CREAS) of five municipalities in the interior of the state of São Paulo. Through critical analysis, it is evident the contradictions between socio-educational and punitive goals. We understand, considering the complexity of the practice that this issue relates to a current socio-historical context marked by the logic of the individualization of social problems, an inheritance of the doctrine of the irregular situation that corroborates with the indications of the literature of the area. Thus, despite advances in the direction of guaranteeing rights, socio-education, from the perspective of the research participants, in the daily life of services, it is dubious between protection and punishment. Thus, from the results of the research, it is possible to affirm that socio-education is effective in the contradiction resulting from its little conceptual precision as well as the difficulties of execution in the daily routine of services. In such a way, most of the socio-educational actions stem from being more punitive. From this perception, it is necessary to improve public policies, development, and collective participation in the construction and application of a proposal for socio-education.

El objetivo de este artículo es reflexionar sobre el sentido de socioeducación y sus contradicciones en la práctica del consejero de educación social. Para eso, partimos de datos de una investigación cualitativa, que utiliza entrevistas como recopilación de datos y la comprensión del papel de los socioeducadores en los Centros de Referencia Especializados en Asistencia Social (CREAS) de cinco municipios en el interior del estado de São Paulo. Las contradicciones entre lo socioeducativo y lo punitivo se evidencian mediante un análisis crítico. Teniendo en cuenta la complejidad de la práctica, se entiende que este tema está relacionado con un contexto socio-histórico aún prevaleciente marcado por la lógica de la individualización de los problemas sociales, la herencia de la doctrina de la situación irregular, corroborando las indicaciones de la literatura del área. Por lo tanto, a pesar de los avances en términos de garantía de derechos, la educación social, desde la perspectiva de los participantes en la investigación, en la vida diaria de los servicios, es dudosa entre la protección y el castigo. Por lo tanto, a partir de los resultados de la investigación, es posible afirmar que la socioeducación es efectiva en la contradicción resultante de su poca precisión conceptual, así como las dificultades de ejecución en la rutina diaria de los servicios. De tal manera, la mayoría de las acciones socioeducativas terminan siendo más punitivas. De esta percepción, es necesario mejorar las políticas públicas, el desarrollo y la participación colectiva en la construcción y aplicación de una propuesta de educación social.

O objetivo deste artigo é refletir sobre o sentido da socioeducação e suas contradições na prática do orientador de medidas socioeducativas. Para tanto, parte-se de dados de uma pesquisa qualitativa, que utiliza entrevistas como coleta de dados e a compreensão do papel dos socioeducadores nos Centros de Referência Especializados em Assistência Social (CREAS) de cinco municípios do interior do estado de São Paulo. Evidencia-se, por meio de uma análise crítica, contradições entre o socioeducativo e o punitivo. Considerando a complexidade da prática, entende-se que essa questão se relaciona com um contexto sócio-histórico vigente marcado pela lógica da individualização dos problemas sociais, herança da doutrina da situação irregular, corroborando as indicações da literatura da área. Desta forma, apesar dos avanços no sentido de garantia de direitos, a socioeducação, na perspectiva dos participantes da pesquisa, no cotidiano dos serviços, mostra-se dúbia entre a proteção e a punição. Assim, a partir dos resultados da pesquisa, é possível afirmar que a socioeducação se efetiva na contradição decorrente de sua pouca precisão conceitual, bem como das dificuldades de execução no cotidiano dos serviços. De tal maneira, grande parte das ações socioeducativas acabam sendo mais punitivas. A partir desta percepção, faz-se necessário aperfeiçoamento das políticas públicas, desenvolvimento e participação coletiva na construção e aplicação de uma proposta de socioeducação.
SOCIO-EDUCATION: BETWEEN SANCTION AND PROTECTION
SOCIOEDUCACIÓN: ENTRE SANCIÓN Y PROTECIÓN
Keywords: Socioeducation; Socio-educational measures; Public policies; Socioeducação; Medida socioeducativa; Políticas públicas